Improvement of Management Mechanisms in Industrial Enterprises - Akmaljon O'rinov; Mamatojieva Sarvinoz (European Science Publishing, 2023)
The purpose of this article is to study the state of management of industrial enterprises today, identify existing problems and provide our solutions. The current state of the rapidly developing industrial network was thoroughly studied, and the main causes of the identified problems were also covered in the article.
Keywords: Global competition, industrial enterprises, balance, environmental regulation, industry, demand, supply.